2019
DOI: 10.3389/fnagi.2019.00222
|View full text |Cite|
|
Sign up to set email alerts
|

Age-Dependent Relationship Between Plasma Aβ40 and Aβ42 and Total Tau Levels in Cognitively Normal Subjects

Abstract: Both amyloid plaques and neurofibrillary tangles are pathological hallmarks in the brains of patients with Alzheimer’s disease (AD). However, the constituents of these hallmarks, amyloid beta (Aβ) 40, Aβ42, and total Tau (t-Tau), have been detected in the blood of cognitively normal subjects by using an immunomagnetic reduction (IMR) assay. Whether these levels are age-dependent is not known, and their interrelation remains undefined. We determined the levels of these biomarkers in cognitively normal subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 42 publications
6
22
1
1
Order By: Relevance
“…Using Spearman correlation analysis, we found Aβ42 level is negatively correlated with age (r = −0.365, P = 0.005), and the value of Aβ42 × t-tau is negatively correlated with age (r = −0.266, P = 0.046) in the control group. These findings suggest that Aβ42 level as well as Aβ42 × t-tau value decreases according to age growth in healthy subjects, which agree with those of Lue et al (2019b), who showed that plasma Aβ42 decreased as age increased in cognitively normal subjects. These relationships provided evidence that Aβ42 may be involved in the pathophysiology of aging and could act as plasma biomarkers in aging-associated disease.…”
Section: Discussionsupporting
confidence: 90%
“…Using Spearman correlation analysis, we found Aβ42 level is negatively correlated with age (r = −0.365, P = 0.005), and the value of Aβ42 × t-tau is negatively correlated with age (r = −0.266, P = 0.046) in the control group. These findings suggest that Aβ42 level as well as Aβ42 × t-tau value decreases according to age growth in healthy subjects, which agree with those of Lue et al (2019b), who showed that plasma Aβ42 decreased as age increased in cognitively normal subjects. These relationships provided evidence that Aβ42 may be involved in the pathophysiology of aging and could act as plasma biomarkers in aging-associated disease.…”
Section: Discussionsupporting
confidence: 90%
“…Higher plasma tau levels were also associated with older age in our study. These findings are consistent both with the notion that plasma tau is likely a biomarker of neurodegeneration [ 35 ] and that it is positively correlated with age [ 36 ]. We also identified association between older age and TNF α , as previously reported [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…Age may influence the expressions of targeted proteins in the plasma. Plasma levels of the total Tau and Aβ42 levels have modest but significant correlations with chronological age [ 44 ] while there is no significant correlation between age and plasma α-synuclein levels in neurologically healthy controls [ 11 , 22 ]. This age effect was not considered in our machine-learning algorithm, and future classification models incorporating age effects are warranted.…”
Section: Discussionmentioning
confidence: 99%